PEMBERDAYAAN MASYARAKAT ASEMROWO MELALUI PELATIHAN PEMBUATAN KONEKTOR MASKER GUNA MENINGKATKAN EKONOMI KREATIF - Muhammad Nabiel Azra; Dhea Nanda Safira; Indira Kusumawardhani; Desti Agustia Putri; Irma Yuhesti; Dani Fajariyatusyarifah; Ikrima Noka Wardani; Fiiryal Regina Hidayah; Indhi Regitha Pramesti; Melyana Sihotang; Gideon Setyobudiwitjaksono (Nusantara Hasana Journal, 2022)
This community service journal provides ideas on how to empower the community in Asemrowo Village through mask connector training, with the goal of providing knowledge and expertise so that residents who participate in the training can improve the welfare of Asemrowo Village residents following the current pandemic. A group of 32 KKNT-MBKM UPN "Veterans" from East Java created a mask connector training work program employing beads, which were constructed of pearls and plastic in this activity. Twenty individuals from Asemrowo Village came to see the results of this training exercise on constructing mask connectors out of beads. The residents are eager to learn how to manufacture mask connectors. They even came up with new ways to use these beads to construct bracelets and rings. This activity is hoped to be beneficial and implemented as a new business opportunity in Asemrowo Village.